Iatrogenic wounds: a common but often overlooked problem. Issue 1 (1st June 2019) - Cheng, Biao; Tian, Ju; Peng, Yan; Fu, Xiaobing
Abstract: Iatrogenic wounds are a common but often overlooked concept. They can lead to increases in hospital stays, therapy costs, repeat surgeries, and implant removal. If not handled properly, these wounds have a very poor prognosis and will cause serious physical and psychological harm to patients, which may result in medicolegal disputes. In recent years, the incidence of iatrogenic wounds has increased because of (1) an increase in the population of older people owing to increased life expectancy, (2) the continued expansion of surgical indications, (3) an increase in difficult surgeries, and (4) the constant emergence and application of new implantable biomaterials and other therapies. Thus, there is a pressing clinical need to improve the therapy of iatrogenic wounds. However, the difficulty in treating these wounds is considerable due to the emergence of drug-resistant bacteria, the high number of patients with metabolic diseases, and complex complications in patients. In particular, iatrogenic wounds caused by surgical site infections due to implantable biomaterials could lead to material leakage and conflicts regarding whether to retain or remove the implants. This review provides a definition of iatrogenic wounds, describes their characteristics, classifies them, and provides information about the importance of analyzing iatrogenic wounds. We hope that this review will provide useful information for the diagnosis and treatment of iatrogenic wounds and help to reduce their incidence in the future.